Faktor-faktor yang mempengaruhi kualitas kinerja pegawai kantor pertanahan di Kabupaten Rote Ndao - Geraldino A Sayd; Frans Gana; Petrus Kase (Faculty of Social and Political Science, Universitas Airlangga, 2016)
The aim of this research is to analyzes determinant factors (input) and determinant factor (process) to employee working quality (output) in Land Agency in Rote Ndao regency. There are 6 variables used in this research with 6 independent variables and one dependent variable. 6 dependent variables consist of human resources, budget, facility, infrastructure, bureaucracy efficiency, and labor discipline; independent variable is working quality. Population in this research are 30 employees from Land Agency in Rote Ndao regency. Data analysis used in this research is Spearman’s correlation analysis method. This research concludes that the six independet variables have significant influnce toward the dependent variable partially and simultaneously.